Design and Implementation of Low Power Multiplier Using Proposed Two Phase Clocked Adiabatic Static CMOS Logic Circuit - Minal Keote; P. T. Karule (Institute of Advanced Engineering and Science, 2018)
This paper presents a design and implementation of 2*2 array and 4*4 array multiplier using proposed Two Phase Clocked Adiabatic Static CMOS logic (2PASCL) circuit. The proposed 2PASCL circuit is based on adiabatic energy recovery principle which consumes less power. The proposed 2PASCL uses two sinusoidal power clocks which are 1800 phase shifted with each other. The measurement result of 2*2 array proposed 2PASCL multiplier gives 80.16 % and 97.67 %power reduction relative to reported 2PASCL and conventional CMOS logic and the measurement result of 4*4 array proposed 2PASCL multiplier demonstrate 32.88 % and 82.02 %power reduction compared to reported 2PASCL and conventional CMOS logic . Another advantage of the proposed circuit is that it gives less power though the number of transistor in proposed and reported 2PASCL circuit is same. From the result we conclude that proposed 2PASCL technology is advantageous to application in low power digital systems, pacemakers and sensors. The circuits are simulated at 180nm technology mode.